Selective antimicrobial activity of Piper Sarmentosum against Pseudomonas Aeroginosa - Siti Hanisah, Puzi; Abd. Samah, Othman; Abubakar, Sule (New Century Health Publishers, 2011)
Abstract: Increasing awareness of hazards associated with the use of antibiotic and chemical agents has accelerated investigations into plants and their extracts as new sources of antimicrobial agents. Therefore, this study is aimed at determining the antimicrobial activity of Poly Butylene Succinate extracts of Piper sarmentosum leaves and stems against six pathogenic strains associated with humans namely; Escherichia coli, Pseudomonas aeroginosa, Bacillus anthracis, Staphylocuccus aureus, Candida albicans and Candida neoformans by the disc diffusion method. The results revealed potent antimicrobial activity by both the leaves and stem extracts on P. aeroginosa at all the concentrations of the extracts used with an MIC values of 50mg/ml and 100 mg/ml obtained for with the stem and leaves extracts respectively by the micro broth method. The highest activity was exerted by the stem extract at 400mg/ml (20mm) and the least was by the leaves extract at 50mg/ml (9mm) on P. aeroginosa. However these extracts were unable to inhibit the growth of E. coli, B. anthracis, S. aureus, C. albicans and C. neoformans at all the tested concentrations. This confers utility of the extracts in treating infections associated with P. aeroginosa whereas they are unsuitable for infections associated with the other strains tested in this study.